The influence of human resource synergy, project management, and logistics on the implementation of sustainable development in the new capital city - Suprayitno, Degdo (Edelweiss Applied Science and Technology, 2025)
Sustainable development serves as the primary objective in the development of Nusantara Capital City (IKN) as Indonesia’s new capital. This study aims to analyze the influence of human resource (HR) synergy, project management, and logistics on the implementation of sustainable development, with operational efficiency acting as a mediating variable. A quantitative approach was employed, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to examine the relationships among variables. The findings reveal that logistics exerts a significant influence on operational efficiency (path coefficient = 0.788; p < 0.001) and the implementation of sustainable development (path coefficient = 0.406; p < 0.05). HR synergy also demonstrates a significant impact on sustainable development implementation (path coefficient = 0.396; p < 0.001), whereas project management and operational efficiency do not exhibit significant effects on the dependent variable. The analysis of indirect relationships indicates that operational efficiency does not mediate the relationship between the independent variables and sustainable development implementation. This study identifies logistics as the most dominant factor in supporting operational efficiency and sustainability outcomes. Additionally, HR synergy plays a crucial role in enhancing sustainability efforts. However, project management and operational efficiency require strengthened strategies to contribute more effectively.